PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJAWALI KELAS MADRASAH ALIYAH AL-ZAYTUN KECAMATAN GANTAR KABUPATEN INDRAMAYU - Arif Yosodipuro (Sekolah Tinggi Manajemen IMMI, 2018)
Competence and motivation may closedly effect to homeroom teachers. This study was to determine whether there was or not influence of Competence and Motivation to Homeroom Teachers’ Performance of Madrasah Aliyah Al - Zaytun Gantar Indramayu. The research activities were carried out from October 2013 to January 2014. The number of respondents were as many as 30 Homeroom Teachers of Madrasah Aliyah Al - Zaytun Gantar Indramayu, using proportional random sampling method . The Data collection methods used in this reasearch were questionnaires, interviews , observation and documentation . Precentage was used to analyze the data based on the statistical analysis with ANOVA technical analysis using SPSS 12.00 for windows . Based on the analysis using SPSS 12.0 for windows that was obtained by calculating the coefficient table based SPSS version 12.00, then the t-count for N = 30 was equal to 3,436 and 1.697 t-table . So t-count t-table or 3,436 1.697 with probility (significance) = 0.021 . Thus , Ho was rejected and Ha was accepted . Since the value of t-count t-table , it could be concluded that the Competence (variable X1) did have a positive and significant influence on the performance of Homeroom Teachers (Variable Y) . Based on the table by calculating the coefficient of SPSS version 12.00, then the t count for the variable motivation ( X2 ) was 2.435 while the value of t table for N = 30 was equal to 1.697 so t count t table or 2.435 1.697 with probibility (significance) = 0.002 . Thus , Ho was rejected and Ha was accepted . Since the value of t count t table , it could be concluded that the motivation (variable X2) indeed had a positive and significant influence on homeroom teachers’ performance (variable Y). From the result of calculation using ( SPSS ) version 12.00 the ANOVA test or F-test it was found that F-count was larger 11,915 . While the F-table or ( á 0.05 ) for N = 30 was equal to 2.69 with a significant level of 0.00 because 0.00 0.05 . It could be said that the variable Competence (X1), motivation variable (X2) simultaneously had a real influence to the performance variables of homeroom teachers (Y) in Madrasah Aliyah Al - Zaytun Gantar , Indramayu.